PENGARUH L-PROLIN SEBAGAI AGEN EUTEKTIK TERDADAP KELARUTAN DAN DISOLUSI LAMIVUDIN - Silmi, Luthfia
L-proline (PRO) which is a nonessential amino acid can be categorized as a eutectic agent. Eutectic agents themselves are substances that can reduce the melting point of a chemical other than its pure substance. This substance is thought to affect the solubility and dissolution of an antiviral drug, lamivudine (LAMI). In the process, to increase the solubility and dissolution of lamivudine can also be done by the salting process using NaOH (NA). To determine which substances can affect the melting point, screening is done by making a binary phase diagram of the combination of the two substances with various combinations. Then, to strengthen the suspicion that the solubility and dissolution of the substance increases, characterization is done using several instruments such as Fourier Transform Infrared Spectroscopy (FTIR), Powder X-ray Diffractometer (PXRD), Digital Thermal Analysis (DTA), and electrothermal. The result of the analysis has shown that there is an increase of solubility in LAMI-PRO mixture as high as 41,4 times and an increase of dissolution by pH 1,2 as high as 1,2 and 1,11 times in LAMI-PRO and LAMI-PRO-NA mixture.